Examination of oral health quality of life and patient satisfaction in removable denture wearers with OHIP-14 scale and visual analog scale: a cross-sectional study - Büşra Tosun; Nur Uysal (BMC Oral Health)
Abstract Background Oral Health-Related Quality of Life (OHRQoL) is a term that encompasses conditions such as oral health status, living conditions, and function. OHQoL can change with the varying health conditions of the same individual. Many patients cannot afford implants or have anatomical limitations and therefore use traditional removable dentures. There are comparatively few studies investigating OHRQoL and denture satisfaction that include the patients’ sociodemographic data, denture satisfaction and related questions. Aim This study aimed to investigate OHRQoL and patients’ satisfaction with three types of dentures: upper and lower complete dentures, upper and lower partial dentures, and upper complete lower partial dentures. Methods The study was conducted between January 2022 and June 2023, with 150 patients using removable dentures. Patients’ age, gender, education level, place of residence, smoking status, reasons for tooth loss and visiting the clinic, type of denture and the duration of denture use were recorded. Oral Health Impact Profile (OHIP-14) and patient satisfaction with dentures as measured on a Visual Analog Scale (VAS) were used to assess patients’ satisfactions with OHRQoL and dentures respectively. Descriptive statistics, the Shapiro-Wilk normality test, the Mann-Whitney non‐parametric test and the Kruskal-Wallis test were used. Results Statistically significant differences were found between gender, prosthetic type, usage duration and OHIP and VAS scores (p < 0.05). Women’s OHIP scores were higher than men’s, patients using complete dentures had higher scores than those using partial dentures in both jaws, those using dentures for less than 1 year had higher scores than those that had used them for more than 1 year. The analysis revealed no statistically significant differences in OHIP and VAS scores based on age, education level, and place of residence (p > 0.05). Conclusions Patients may find it easier to adapt to removable partial dentures compared to complete dentures. Therefore, in prosthetic planning, dentists should prioritize preserving existing teeth. Regardless of the type of prosthesis, patients adapt to their prostheses over time, leading to increased satisfaction with prolonged use. Since individuals do not have a habit of visiting the dentist when there is no known problem, dentists should encourage patients to attend regular dental check-ups.